2017
DOI: 10.1002/jum.14231
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Transverse Tracheal Sonography During Emergent Intubation by Emergency Medicine Resident Physicians

Abstract: Objectives Establishing a definitive airway is often the first step in emergency department treatment of critically ill patients. Currently, there is no agreed upon consensus as to the most efficacious method of airway confirmation. Our objective was to determine the diagnostic accuracy of real‐time sonography performed by resident physicians to confirm placement of the endotracheal tube during emergent intubation. Methods We performed a prospective cohort study of adult patients in the emergency department un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Moreover, Lahham et al [19] performed real-time transverse tracheal sonography during intubation to evaluate correct ETT placement and detected correct tracheal placement in 94.4% of patients, while 5.6% of intubations were interpreted as esophageal, and concluded that US conferred sensitivity and specificity rates of 98.5% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lahham et al [19] performed real-time transverse tracheal sonography during intubation to evaluate correct ETT placement and detected correct tracheal placement in 94.4% of patients, while 5.6% of intubations were interpreted as esophageal, and concluded that US conferred sensitivity and specificity rates of 98.5% and 75%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…157 The ASA Closed Claims Project shows that bronchial intubations account for 4% of respiratory claims in children compared with 2% in adults. 158 Point-of-care LUS correctly identifies endobronchial intubation in 95%-100% of children. 153 159 160 Diagnosis of an interstitial syndrome and pneumothorax is similar to adult data.…”
Section: Airway and Lusmentioning
confidence: 96%
“…Adult and pediatric literature reveal a sensitivity and specificity of 98.5% to 100% and 75% to 100%, respectively, for this method. [84][85][86][87] Obesity, abnormal airways, and short necks may limit visibility. This technique has also been described in extremely preterm infants.…”
Section: Figure 14mentioning
confidence: 99%